ANALYSIS OF ULI BRAND BRANDING STRATEGY IN MAINTAINING THE POSITION OF THE MINERAL WATER MARKET IN PEMATANGSIANTAR - Liharman Saragih; Vivi Anggraini Tan; Anggi Dwi Fanny; Dwi Nur Azmi; Seiman Krisman Tafonao (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the branding strategy implemented by ULI in maintaining its market position in the bottled drinking water industry in Pematangsiantar . The research uses a qualitative approach with a literature study method by collecting and analyzing various secondary data sources such as books, scientific journals, articles, and internet sources related to branding strategies and the bottled drinking water industry. The results of the study indicate that ULI's success in maintaining its market position is influenced by the implementation of strong, consistent, and sustainable branding strategies. ULI has succeeded in building strong brand positioning, high brand awareness, positive brand image, and consumer loyalty. In addition, other supporting factors such as consistent product quality, extensive distribution networks, competitive pricing, and the company's ability to adapt to market competition also contribute significantly to maintaining market share. The study concludes that the combination of effective branding strategies and supporting factors has become the main strength for ULI in maintaining its existence amid increasingly competitive market competition in the bottled drinking water industry in Pematangsiantar .